Positive HCMV DNAemia in stem cell recipients undergoing letermovir prophylaxis is expression of abortive infection. Issue 4 (8th February 2021) - Cassaniti, Irene; Colombo, Anna A.; Bernasconi, Paolo; Malagola, Michele; Russo, Domenico; Iori, Anna P.; Girmenia, Corrado; Greco, Raffaella; Peccatori, Jacopo; Ciceri, Fabio; Bonifazi, Francesca; Percivalle, Elena; et al.
Abstract: Letermovir (LMV) inhibits HCMV replication by binding to components of the HCMV‐terminase complex showing a potential role in prevention of HCMV‐related complications in allogenic hematopoietic stem cell transplant recipients (allo‐HSCTRs). However, little is known about breakthrough HCMV infection and the relevance of HCMV DNAemia during prophylaxis. We reported the results of a multicenter prospective study involving five Italian centers in the management of HCMV DNAemia in 75 adult HCMV‐seropositive allo‐HSCTRs undergoing LMV prophylaxis. The aim of the present study was to characterize the presence of real HCMV reactivation during LMV prophylaxis. Then, the presence of circulating infectious HCMV particles was determined by virus isolation and degradation of free‐floating viral DNA. This report provides the first evidence that during LMV prophylaxis the clinical relevance of HCMV DNAemia should be critically considered. Abstract : Detection of human cytomegalovirus DNAemia in haematopoietic stem cell transplant recipients receiving prophylactic letermovir is due to free‐floating and noninfectious cytomegalovirus DNA, suggesting abortive replication that does not justify any treatment change.